The Impact of Using a ChatGPT-based application to Enhance Saudi Students’ EFL Vocabulary Learning - Aldowsari, Boshra Ibrahim; Aljebreen, Saad Ghareeb (International Journal of Language and Literary Studies, 2024)
This study investigates the impact of using a ChatGPT-based application on enhancing vocabulary learning among Saudi high school students. A quasi-experimental research design was adopted, involving an experimental group and a control group. Data were collected from 57 female high school students using pre- and post- tests and a follow-up questionnaire to explore vocabulary learning and students’ attitudes. The findings of the study revealed statistically significant improvement in learning vocabulary among the experimental group compared to the control group. In addition, the students expressed positive attitudes toward the application. In general, the results show the great potential that ChatGPT would bring to teaching and learning of EFL vocabulary.